E-AVIATION ENGLISH LEARNING - Muhammad Rizqisya, Daffa; Rochmawati, Laila; Hadi Rantelinggi, Parma; Putra, Iwansyah; Ratna Sari, Dewi (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The IELP (ICAO English Language Proficiency) examination is an important requirement for graduation from the D3 Aeronautical Communication program. It is used to assess the English language proficiency of Air Communication personnel. However, many students still struggle to adequately prepare for the IELP examination. With the rapid advancement of technology, the development of the E-Aviation English Learning website has emerged as a new innovation to serve as a learning platform and facilitate the preparation of students for the IELP examination. The research method employed in the creation of this website is Research and Development, utilizing the ADDIE development method, which consists of Analysis, Design, Development, Implementation, and Evaluation. Black box testing was used as the testing technique, and qualitative descriptive analysis was conducted using triangulation through interviews, observations, and documentation. The result of this research is the E-Aviation English Learning website, which contains materials tailored to the needs of the students, along with features for instructors and administrators to monitor students' learning progress. The conclusion of this research is that the website meets the expected requirements; however, further development is still necessary to improve its features and user interface, aiming to provide a more convenient learning experience for the students